Dragon on trial - Sutherland, Tui, 1978-; Sutherland, Kari H. (Sutherland, Tui, 1978- Menagerie, 2015)
At the Menagerie in Xanadu, Wyoming, the goose who lays the golden eggs is missing and a dragon named Scratch is blamed. Zoe Khan, whose family cares for the Menagerie, and her friend Logan Wilde are sure Scratch has been framed and set out to prove his innocence.